Pathogenic mucorales: Deciphering their cell wall polysaccharidome and immunostimulatory potential - Mathieu Lepas; Julia Marcondes Figueiredo; Sarah Dellière; Sarah Sze Wah Wong; Dea Garcia-Hermoso; Magalie Duchateau; Mariette Matondo; Fanny Lanternier; Vishukumar Aimanianda (Virulence, 2025)
Mucormycosis is an emerging infection caused by pathogenic filamentous fungal species belonging to the Order Mucorales. Mortality associated with mucormycosis is significantly high in patients with compromised immunity. As cell wall is the first fungal component to interact with the host immune system, we characterized cell wall organization and composition of the three most prevalent pathogenic species of Mucorales, Rhizopus arrhizus, Mucor circinelloides, and Lichtheimia corymbifera and studied their immunomodulatory potential. Staining and lectin-/immunolabeling indicated that the spores and germ-tubes of these three Mucorales species have surface-exposed mannans, while germ-tubes showed distinctly distributed β-1,3-glucan. Gas chromatography analysis of the cell wall indicated that glucose polymer is the major fibrillar polysaccharide present in the three species, whereas amorphous components were species-dependent. Specific enzymatic digestion followed by chromatography analysis indicated that β-1,3-glucan, β-1,6-glucan, and amylase digestible glucan constitute firbrillar polysaccharides. Stimulation of human peripheral blood mononuclear cells or THP-1 (human leukemic monocytic) cells with spores or extracted cell wall polysaccharides resulted in the release of pro-inflammatory cytokines regardless of the Mucorales species. Together, the Mucorales species analyzed in this study show a common and species-specific cell wall composition. The cell wall polysaccharides are highly pro-inflammatory, suggesting that undue or excessive inflammation may contribute to the immunopathology of mucormycosis.